Risk Factors for Chronic Disease Among Rural Vietnamese Adults and the Association of These Factors With Sociodemographic Variables: Findings From the WHO STEPS Survey in Rural Vietnam, 2005 - Hoang Van Minh, MD, PhD; Peter Byass, PhD; Dao Lan Huong, MD, PhD; Nguyen Thi Kim Chuc, PhD; Stig Wall, PhD (Centers for Disease Control and Prevention, 2007)
IntroductionChronic diseases have emerged as a major health threat to the world's population, particularly in developing countries. We examined the prevalence of selected risk factors for chronic disease and the association of these risk factors with sociodemographic variables in a representative sample of adults in rural Vietnam.MethodsIn 2005, we selected a representative sample of 2000 adults aged 25 to 64 years using the World Health Organization's STEPwise approach to surveillance of chronic disease risk factors. We measured subjects' blood pressure, calculated their body mass index (BMI), and determined their self-reported smoking status. We then assessed the extent to which hypertension, being overweight (having a BMI ≥25.0), smoking, and various combinations of these risk factors were associated with subjects' education level, occupational category, and economic status.ResultsMean blood pressure levels were higher among men than among women and increased progressively with age. The prevalence of hypertension was 23.9% among men and 13.7% among women. Sixty-three percent of men were current smokers, and 58% were current daily smokers; less than 1% of women smoked. Mean body mass index was 19.6 among men and 19.9 among women, and only 3.5% of the population was overweight. Education level was inversely associated with the prevalence of hypertension among both men and women and with the prevalence of smoking among men. People without a stable occupation were more at risk of having hypertension than were farmers and more at risk of being overweight than were farmers or government employees. Hypertension was directly associated with socioeconomic status among men but inversely associated with socioeconomic status among women.ConclusionRural Vietnam is experiencing an increase in the prevalence of many risk factors for chronic diseases and is in urgent need of interventions to reduce the prevalence of these risk factors and to deal with the chronic diseases to which they contribute.